FAW-Volkswagen Audi : leader (1987-2000) - McFarlan, F. Warren (Franklin Warren); Jiao, Jie; Cao, Shanshan; Dong, Meichen; Jiao, Hao (London : Tsinghua University School of Economics and Management, 2016)
The FAW-Volkswagen Audi "trilogy" case describes Audi's development history in China and the problems it faces currently, as well as demonstrating the strategies employed by FAW-Volkswagen Audi in their thirty year business partnership. The case illustrates the difficulties faced by Audi and FAW in setting up a supply chain and how the different companies resolved their conflicting cultures to quality to become profitable and mass produce cars.
Originally Published InWarren, F. W., Jiao, J., Cao, S., Dong, M., & Jiao, H. (2016). FAW-Volkswagen Audi: Leader (1987-2000). 0-516-311. Beijing: Tsinghua SEM China Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Volkswagenwerk; Audi AG; Automobile industry and trade -- China; Industrial efficiency; Factory management